Muscle adaptations in acute SCI following overground exoskeleton + FES training: A pilot study - Hohl, Kristen; Smith, Andrew C.; Macaluso, Rebecca; Giffhorn, Matthew; Prokup, Sara; O’Dell, Denise R.; Kleinschmidt, Lina; Elliott, Jim M.; Jayaraman, Arun (Frontiers in Rehabilitation Sciences, 2022)
Objective: To evaluate the combined effects of robotic exoskeleton and functional electrical stimulation (FES) training on muscle composition during over-ground gait training in persons with acute spinal cord injury (SCI). Design: Randomized crossover pilot study. Setting: Inpatient-rehabilitation Hospital. Participants: Six individuals with acute SCI. Intervention: Participants were randomized to either receive training with the Ekso® Bionics exoskeleton combined with FES in addition to standard-of-care or standard-of-care alone. Outcome Measures: The main outcome measures for the study were quantified using magnetic resonance imaging (MRI), specifically, lower extremity muscle volume and intramuscular adipose tissue (IMAT). Static balance and fall risk were assessed using the Berg Balance Scale. Results: Significant improvements were observed in muscle volume in the exoskeleton intervention group when compared to only standard-of-care (p<0.001). There was no significant difference between the groups in IMAT even though the intervention group saw a reduction in IMAT that trended towards statistical significance (p=0.07). Static balance improved in both groups, with greater improvements seen in the intervention group. Conclusions: Early intervention with robotic exoskeleton may contribute to improved muscle function measured using MRI in individuals with acute SCI.